2004
DOI: 10.1038/sj.leu.2403337
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of p27KIP1 expression in cyclin D1 positive lymphoproliferative disorders

Abstract: Nodal mantle cell lymphoma (MCL) is a well-defined entity, but non-nodal leukemic cyclin D1 positive lymphoproliferative disorders have been reported and their relationship with MCL remains controversial and their prognosis heterogeneous. We prospectively studied the expression of cyclin D1 in CD5 positive leukemic B lymphoproliferative disorders at diagnosis and identified 65 cases overexpressing cyclin D1. We did not distinguish any clinical or biological criteria allowing one to identify a non-MCL group. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
2
15
1
2
Order By: Relevance
“…They also suggest that NF-κΒ and STAT3 pathways may cooperate to play an important role in MCL proliferation, as described in diffuse large B-cell lymphoma. Some studies identified IGHV mutational status as a relevant prognostic factor in MCL, 3,[26][27][28] suggesting an involvement of antigen stimulation in the course of the disease. In these studies, patients with mutated IGHV appeared to have a better clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggest that NF-κΒ and STAT3 pathways may cooperate to play an important role in MCL proliferation, as described in diffuse large B-cell lymphoma. Some studies identified IGHV mutational status as a relevant prognostic factor in MCL, 3,[26][27][28] suggesting an involvement of antigen stimulation in the course of the disease. In these studies, patients with mutated IGHV appeared to have a better clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the levels of the protein correlated with cyclin D1 in all MCL tumors and cell lines analyzed. Conversely, previous studies have reported an overall inverse correlation between these 2 proteins in most neoplastic models and a low frequency of p27 KIP1 expression in MCL (5)(6)(7). In these studies, the methods used for p27 KIP1 detection did not distinguish tumor cells from residual normal cells and their sensitivity was remarkably weak.…”
Section: Discussionmentioning
confidence: 69%
“…In this line, preclinical studies have proposed that CDK-independent functions of cyclin D1 may account for its oncogenic and antiapoptotic properties (4), suggesting that other(s) partner(s) of cyclin D1 could represent attractive therapeutic targets. Among these partners, the CDK inhibitor p27 KIP1 is strongly expressed in the highly proliferative and aggressive blastoid MCL variants while is only present in a minority of the good prognosis and low proliferative MCL tumors (5)(6)(7). It was thus proposed that mantle cell lymphomagenesis may result, at least in part, from the ability of the overexpressed cyclin D1 to buffer changes of p27 KIP1 levels, thereby rendering ineffective the p27 KIP1 -mediated inhibition of cellular growth (8).…”
Section: Introductionmentioning
confidence: 99%
“…Conforme exposto, a invasão do sangue periférico no linfoma de células do manto é relativamente freqüente, e o desenvolvimento de uma franca fase leucêmica é identificado em cerca de um terço dos casos (ARGATOFF et al, 1997;BOSCH et al, 1998;LETESTU et al, 2004;MARTINEZ-CLIMENT et al, 2001;ORCHARD et al, 2003;WONG et al, 1999). Ainda que controverso, o critério mais aceito para definir a fase leucêmica dos linfomas não-Hodgkin indolentes de imunofenótipo B é a detecção de linfocitose persistente acima de 5 × 10 9 /L, na ausência de outras doenças que possam justificar esse achado (BENNETT et al, 1989;MARQUES, 1997).…”
Section: Características Clínicas E Imunofenotípicasunclassified
“…Ainda que controverso, o critério mais aceito para definir a fase leucêmica dos linfomas não-Hodgkin indolentes de imunofenótipo B é a detecção de linfocitose persistente acima de 5 × 10 9 /L, na ausência de outras doenças que possam justificar esse achado (BENNETT et al, 1989;MARQUES, 1997). O quadro clínico do linfoma de células do manto em fase leucêmica é bastante variável, uma vez que já foram descritas evoluções clínicas tanto indolentes, quanto extremamente desfavoráveis (ARGATOFF et al, 1997;BOSCH et al, 1998;COHEN et al, 1998;DE OLIVEIRA;LETESTU et al, 2004;MARTINEZ-CLIMENT et al, 2001;MOLINA et al, 2000;ORCHARD et al, 2003;VANDENBERGHE et al, 1997;WEISENBURGER et al, 2000;WONG et al, 1999 REED, 1991;ROSENBERG et al, 1991;SCHUURING et al, 1992;WITHERS et al, 1991). Inicialmente, a ciclina D1 foi aceita como provável produto do gene BCL1 apenas porque não se demonstrou nenhuma outra região codificante entre o ponto de quebra da translocação t(11;14)(q13;q32) e o lócus da ciclina D1 (ROSENBERG et al, 1991;WITHERS et al, 1991).…”
Section: Características Clínicas E Imunofenotípicasunclassified